EFEKTIVITAS KALSIUM KARBONAT DENGAN VARIASI KETEBALAN MEDIA DALAM MENGURANGI KADAR KADMIUM PADA LARUTAN PUPUK - Bekti Kusuma Wijayanti; Nur Endah Wahyuningsih; Budiyono Budiyono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Farmer’s activity to fertilize plant can decrease the quality of the river. Fertilizers contain substances that are difficult to degrade. One of them is cadmium heavy metal (Cd) which can damage the ecosystem and cause health problems. To reduce cadmium levels in fertilizer water was by employing the filtration method using calcium carbonate powder. The purpose of this study was to determine the effectiveness of calcium carbonate powder to reduce cadmium in fertilizer solution. Based on Government Regulation No. 82 of 2001, the threshold value for cadmium on agricultural land is 0.01 mg/l. This type of research design was a quasi experiment with Non Randomized Control Group Pretestt-Postest Design. The independent variable in this study was the variation in thickness of calcium carbonate powder by 40 cm, 50 cm and 60 cm. The dependent variable was the cadmium level in SP-36 fertilizer solution as much as 9 liters. The statistical test used was the One Way Anova test (α = 0.05). The test results showed that the cadmium level in the solution before treatment was 1.820 mg/l and the control was 1,800 mg/l. There were differences in cadmium levels in fertilizer solutions with variations in thickness of calcium carbonate powder. The most optimal thickness variation was 60 cm thickness with 63.415% effectiveness. The thickness of the calcium carbonate media has not been effective in reducing cadmium levels in the fertilizer solution according to the predetermined threshold value.